The Contrast on Instagram Captions: A Language Style Analysis in Sociolinguistics - Winda Septiani; Fitri Rakhmawati (Journey: Journal of English Language and Pedagogy, 2025)
Language style is a rhetorical tool aimed at persuading or influencing audiences in both speech and writing. Additionally, there is a close, reciprocal relationship between language style and vocabulary. This study examines the use of contrast language styles in Instagram captions written by Taylor Swift, employing a descriptive qualitative method and Tarigan’s (2009) framework. The data consist of 37 captions posted between February and November 2024. The analysis reveals 66 instances of contrast language styles, with Hyperbole (46.97%) as the most dominant, followed by Climax (31.82%), Litotes (10.61%), Paradox (6.06%), Oxymoron (4.55%), and Irony (0%). These stylistic choices reflect Swift’s rhetorical strategy to enhance emotional resonance and engagement with her audience. The findings highlight the role of contrastive styles in shaping online persona and social media communication within a sociolinguistic context.